A descriptive analysis of shoulder muscle activities during individual stages of the Turkish Get-Up exercise. Issue 1 (January 2019) - St-Onge, Eric; Robb, Andrew; Beach, Tyson A.C.; Howarth, Samuel J.
Abstract: The Turkish Get-Up (TGU) is a complex and multi-planar exercise; the performer begins in a supine lying position, progresses toward upright standing through a series of 7 stages while holding a mass overhead in one hand, and returns to the original supine lying position through a reversal of the same 7 stages. A descriptive analysis of shoulder muscle activity during the TGU may provide insight toward its use in training and rehabilitation contexts. Our objectives were to: (1) describe the activity patterns from a subset of muscles that span the glenohumeral joint during individual stages of the TGU, and (2) interpret these patterns through comparisons between left- and right-side muscles, and between the up and down phases of the TGU. Twelve individuals with at least one-year experience performing the TGU were included in this study. Surface electromyographic (EMG) recordings were bilaterally obtained from 8 glenohumeral muscle groups while participants performed ten trials of the TGU with a kettlebell in their right hand. Instants representing the start and end of each TGU stage were identified from a synchronized video for each trial, and EMG activities for each muscle were integrated over the duration of each stage. Average integrated EMG and within-participant coefficients of variation were calculated. Overall, the greatest muscular demand occurred during the second (press to elbow support) and fifth (leg sweep) stages. Activities from muscles on the ipsilateral side to the kettlebell (right-side) were greater during stages when the contralateral upper limb did not contribute to supporting the body; however, contralateral (left-side) muscles were invoked during stages when the non-kettlebell-bearing forearm or hand contributed to supporting the body. The results suggest the importance of training both phases of the TGU to gain the most benefit from the exercise and highlights the asymmetric nature of the exercise, which may be particularly relevant for athletes engaged in activities with rotational demands.